Phytochemical Studies Of Aqueous And Methanol Extracts Of Carica Papaya Leaves - Laila M Abdelrahim; Siti NS Abdul Jalil; Zahidah Abu Seman; Noradilah S Abdullah; Zetty Nadia Mohd Zain; Fadlul Azim Fauzi Mansur (SAS Publishers, 2024)
Non-Indexed Publication